Pengaruh Kecerdasan Intelektual, Fasilitas dan Kecerdasan intelektual Terhadap Hasil Belajar Peminatan Ilmu-ilmu Sosial - Rusfandi; Sya'Roni; Sudi Dul Aji (Direktorat Pascasarjana Universitas PGRI Kanjuruhan Malang, 2021)
This research is to: 1. Analyze the effect of intellectual intelligence, facilities, and learning motivation on learning outcomes. 2. Intellectual intelligence of learning outcomes. 3. Facilities for learning outcomes. 4. motivating learning towards learning outcomes. This study uses a quantitative approach with a population of class XI IPS students at Al-Muniri Pamekasan High School, sampling techniques using a total sampling of 40 respondents. Research instruments using questionnaires and documents. Data analysis techniques consist of multiple regression analysis, classic assumption tests and hypothesis testing. Hypothesis testing results show: 1). There is a significant influence of intellectual intelligence, facilities and learning motivation on learning outcomes that is 80.1%. 2). There is a significant influence of intellectual intelligence, on learning outcomes. 3). There is a significant influence of facilities on learning outcomes. 4). There is a significant influence of learning motivation on learning outcomes. While the remaining 19.9% ​​is influenced by other variables not included in this research model.